2008
DOI: 10.1002/elps.200700644
|View full text |Cite
|
Sign up to set email alerts
|

Polyacrylamide‐based monolithic capillary column with coating of cellulose tris(3,5‐dimethylphenyl‐carbamate) for enantiomer separation in capillary electrochromatography

Abstract: A hydrophilic chiral capillary monolithic column for enantiomer separation in CEC was prepared by coating cellulose tris(3,5-dimethylphenyl-carbamate) (CDMPC) on porous hydrophilic poly(acrylamide-co-N,N'-methylene-bisacrylamide) (poly(AA-co-MBA)) monolithic matrix with confine of a fused-silica capillary. The coating conditions were optimized to obtain a stable and reproducible chiral stationary phase for CEC. The effect of organic modifier of ACN in aqueous mobile phase for the enantiomer separation by CEC w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 44 publications
2
41
0
Order By: Relevance
“…The result of baseline separation of benzoin demonstrated that the chiral selector of CDMPC was well coated onto the hybrid monolith matrices. Compared to the reported data on the CDMPC coated onto pure silica monolith [25] or organic monolith [30], the resolution and efficiency on this hybrid monolith was remarkably lower. The same result was also observed for enantioseparation of benzoin with CLC, as shown in Fig.…”
Section: Effects Of Coating Conditions On Enantioseparationmentioning
confidence: 60%
See 2 more Smart Citations
“…The result of baseline separation of benzoin demonstrated that the chiral selector of CDMPC was well coated onto the hybrid monolith matrices. Compared to the reported data on the CDMPC coated onto pure silica monolith [25] or organic monolith [30], the resolution and efficiency on this hybrid monolith was remarkably lower. The same result was also observed for enantioseparation of benzoin with CLC, as shown in Fig.…”
Section: Effects Of Coating Conditions On Enantioseparationmentioning
confidence: 60%
“…The poor efficiency in CEC may be due to the following reasons. In this case, a blank section of capillary with 8.5 cm long was required to fabricate a detection window for on-column CEC analysis and detection, which was different from the on-column detection mode in either pure silica monolith [25] or organic monoliths [30] coated with CDMPC. As a result, the CP-silica monolithic matrices at the interface were not homogeneous, perhaps resulting from the solvent evaporation in the sol-gel process.…”
Section: Effects Of Coating Conditions On Enantioseparationmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of HPLC separations for a large number of chiral compounds in different classes on polysaccharide-immobilized silica [17][18][19][20] and polymer columns. 21 The polysaccharide-based columns can be used in normal phase, polar organic and reversed-phase mode.…”
Section: Introductionmentioning
confidence: 99%
“…HILIC [46] [47] Fused-Silica-Polyacrylamide-based Enantiomer separation CEC [48] Fused-vinylbenzyl trimethylammonium-cyclodextin-based Acidic compound screening CEC [49] β-Cyclodextrin-silica based Enantioseparation LC [50] Zwitterionic Organic-Silica-based Polar compounds HILIC [51] IEC: Ion-Exchange Chromatographic; CEC: Capillary Electrochromatography; AEC: Anion Exchange Chromatography; HPAC: High-Performance Affinity Chromatography; LC: Liquid chromatography; HIC: Hydrophilic interaction chromatography; HILIC: Hydrophilic-Interaction Liquid Chromatography.…”
Section: Introductionmentioning
confidence: 99%